A Reflection on Initiatives for Teachers’ Professional Development Through Language Assessment Literacy - Frank Giraldo (Profile: Issues in Teachers' Professional Development)
In this reflection article I examine language assessment literacy initiatives and their possible impact on teachers, and I discuss the connections that exist between language assessment literacy and teachers’ professional development. I explain that training for language assessment literacy may primarily foster teachers’ knowledge and skills and, secondarily, principles for language assessment (e.g., fairness). In conclusion, existing language assessment literacy initiatives, while limited in number, have the potential to advance teachers’ language assessment literacy overall and contribute to their professional development. Thus, this article may be useful to language teacher educators, particularly in the Colombian context.